Screening Solutions Of Multimonopole By Unit Charge Antimonopoles. - Teh, Rosy; Wong, Khai Ming (2004)
We would like to show in this paper that there exist a whole range of screening solutions of multirnonopole by unit charge antimonopoles in the SU(2) Yang-Mills-Higgs theory.